Preconditioning in an Inflammatory Milieu Augments the Immunotherapeutic Function of Mesenchymal Stromal Cells - Luis A. Rodriguez; Arezoo Mohammadipoor; Lucero Alvarado; Robin M. Kamucheka; Amber M. Asher; Leopoldo C. Cancio; Ben Antebi (Cells, 2019)
Multipotent mesenchymal stromal cells (MSCs) have emerged as potent therapeutic agents for multiple indications. However, recent evidence indicates that MSC function is compromised in the physiological post-injury milieu. In this study, bone marrow (BM)- and adipose-derived (AD)-MSCs were preconditioned in hypoxia with or without inflammatory mediators to potentiate their immunotherapeutic function in preparation for in vivo delivery. Human MSCs were cultured for 48 hours in either normoxia (21% O2) or hypoxia (2% O2) with or without the addition of Cytomix, thus creating 4 groups: 1) normoxia (21%); 2) Cytomix-normoxia (+21%); 3) hypoxia (2%); and 4) Cytomix-hypoxia (+2%). The 4 MSC groups were subjected to comprehensive evaluation of their characteristics and function. Preconditioning did not alter common MSC surface markers; nonetheless, Cytomix treatment triggered an increase in tissue factor (TF) expression. Moreover, the BM-MSCs and AD-MSCs from the +2% group were not able to differentiate to chondrocytes and osteoblasts, respectively. Following Cytomix preconditioning, the metabolism of MSCs was significantly increased while viability was decreased in AD-MSCs, but not in BM-MSCs. MSCs from both tissues showed a significant upregulation of key anti-inflammatory genes, increased secretion of IL-1 receptor antagonist (RA), and enhanced suppression of T-cell proliferation following the Cytomix treatment. Similarly, following a lipopolysaccharide challenge, the Cytomix-treated MSCs suppressed TNF-α secretion, while promoting the production of IL-10 and IL-1RA. These preconditioning approaches facilitate the production of MSCs with robust anti-inflammatory properties. AD-MSCs preconditioned with Cytomix under normoxia appear to be the most promising therapeutic candidates; however, safety concerns, such as thrombogenic disposition of cells due to TF expression, should be carefully considered prior to clinical translation.